Implementation of the Storytelling Method in Islamic Religious Education to Develop the Spiritual Intelligence of Grade XI Students at State Vocational High School 2 Sukoharjo - Hanif Fawwas Ramadhan; Meti Fatimah (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2026)
This study analyzes the implementation of the storytelling method in Islamic Religious Education and identifies its supporting and inhibiting factors in developing the spiritual intelligence of Grade XI students at State Vocational High School 2 Sukoharjo. The study employed a descriptive qualitative approach with a case study design. The research participants consisted of Islamic Religious Education teachers, Grade XI students, and the vice principal for curriculum affairs, selected through purposive sampling. Data were collected through non-participant observation, semi-structured interviews, and documentation. Data analysis involved data condensation, data display, and conclusion drawing and verification. Data credibility was strengthened through source and technique triangulation. The findings show that storytelling was implemented through planning, story delivery, value reflection, and evaluation. Teachers used stories of prophets, companions, and Islamic figures relevant to the learning materials. Storytelling increased students’ attention, participation, understanding, and ability to draw lessons from the stories. The development of spiritual intelligence was reflected in stronger motivation to worship, discipline, responsibility, empathy, social concern, and awareness of Islamic values. Its implementation was supported by teacher competence, the flexibility of the Independent Curriculum, learning facilities, student enthusiasm, and a religious school environment. Its limitations included uneven storytelling skills, diverse student characteristics, limited instructional time, and external social influences.